CRITICAL STATISTICS OF ENERGY LEVEL IN DISORDERED SYSTEMS: I. ORTHOGONAL SYMMETRY CLASS - Zharekeshev, I. Kh. (Recent Contributions to Physics, 2017)
The statistics of electronic levels of discrete spectra of disordered solids at the critical point of the metal-insulator transition are investigated. The single-parameter scaling for the orthogonal symmetry is established.